Internship Program for University Student Skill Development: A Case Study in UIN Sunan Kalijaga - Santoso, Raliandana Louise; Luthfi, Muhammad Ja’far (Proceeding International Conference on Religion, Science and Education, 2022)
Indonesian university graduates frequently encounter challenges after being employed. Many graduates have not had some skills needed to manage their tasks in the real workplace. Prospective undergraduates are expected to prepare themselves to face the demands of the workplace by having abilities related to their fields, being able to develop knowledge, and having broad insight so that they can compete with other graduates in the workplace. This issue encourages universities to continue to improve the quality of their graduates. One of the programs launched by the Faculty of Science and Technology of UIN Sunan Kalijaga to improve students’ soft skills was the internship program. This study aims to review whether the implementation of this internship program has an impact on improving the skills and competencies of students who had participated in this program.